Overview of employment issues after graduation of Sociology Department - Trade Union University - Cù Thị Thanh Thúy, (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Summary: This study surveyed 251 Sociology University graduates before 2017 with a convenient sampling method. The methods used to analyze primary data include descriptive statistics, two-variable correlation analysis. The research results show that students with jobs have a high percentage of subjects, the time for finding jobs is not too long, with types of jobs related to education and training, mass organizations, or in Social and political organizations predominate. Two important job search channels, useful support for students after graduation are through family, friends, relatives. However, there are still many students who work in different fields, which are not suitable with their professional knowledge and skills.